The residential architecture of Nikonion. The results of archaeological research 2009-2011 - Głuszek, Inga; Augustyniak, Jan (Acta Archaeologica Lodziensia, 2022)
As a result of archaeological research carried out in 2008-2011 in ancient Nikonion, the settlement phases were revealed, referring to the declining phase of settlement of the city, the late and early Hellenistic and Late Classical periods. The declining phase dates back to the 1st-3rd century BC. Registered monuments indicate the presence of stone structures. However, due to the intensive agricultural exploitation of this place in the nineteenth and early twentieth centuries, the exposed remains of the structure are badly damaged. They do not allow for the reconstruction of the buildings’ form, size and spatial development. The next settlement level is poorly preserved in architectural objects but manifests in the uncovered source material, mainly table ceramics. The most interesting, due to the state of preservation, are the remnants of architecture dating back to the early Hellenistic period. As a result of the research, a house was found consisting of at least six rooms with partially preserved stone and clay floors. The level relating to the Classical period was captured only as a result of surveys. However, it indicates a different spatial layout of the emerging architecture. The article presents the remains of architectural objects referring to individual phases and source material, allowing for their chronological interpretation.